A Review of Wind Energy Output Simulation for New Power System Planning - Liu, Xinmiao; Yue, Yuan; Huang, Xin; Xu, Wei; Lu, Xun (Frontiers in Energy Research, 2022)
The uncertain and volatile nature of wind energy have brought huge challenges to power system planning and operation. Therefore, it is necessary to model the wind power output. In this paper simulation models of wind energy output for new power system planning are reviewed. We begin by discussing the characteristics of wind power output, and then introduce the wind power output simulation model based on different application scenarios that are based on probability and time series. Finally, the directions for further research in the future are anticipated.